(untitled) (London, 1994)
Aquatic Toxicology examines research findings on the chronic effects of pollutants on aquatic species. Understanding these chronic effects is vital to determining the impact of small concentrations of pollutants on aquatic life in rivers, estuaries, lakes, and coastal waters. Featuring research from renowned experts in the field, this book evaluates modern techniques in the fields of molecular biology and biochemistry. It is indispensable to aquatic toxicologists, aquatic biochemists, fisheries scientists, industrial chemists, and researchers at federal, state, and university levels.
Keywords: Molecular toxicology,Fishes,Aquatic organisms; Effect of water pollution on,Effect of water pollution on